2018
DOI: 10.1007/s10750-018-3799-1
|View full text |Cite
|
Sign up to set email alerts
|

Modelling interactions of fish, fishers and consumers: should bycatch be taken into account?

Abstract: Consumers' preferences coupled with available fishing technology determine fisheries' harvests and impacts on the ecosystem. In this paper, I investigate the effects of unintended catch, or bycatch, on consumption decisions and harvests. To this end, a multi-species coupled ecosystem economy model including consumer preferences is extended to also include bycatch in harvesting. The resulting equilibria and dynamics of the model are solved analytically. This allows demonstration of the effects of bycatch not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Related to assessments, Carpenter (2019) showed the impact of governance measures on oil pollution over several decades. Supporting Theme 3 on sustainability, Blanz (2019) showed that in economic modelling of fisheries, bycatch should be accounted for when modelling interactions of fish, fishers, and consumers.…”
Section: This Special Issuementioning
confidence: 99%
“…Related to assessments, Carpenter (2019) showed the impact of governance measures on oil pollution over several decades. Supporting Theme 3 on sustainability, Blanz (2019) showed that in economic modelling of fisheries, bycatch should be accounted for when modelling interactions of fish, fishers, and consumers.…”
Section: This Special Issuementioning
confidence: 99%